Developmental trajectories of offenders convicted of fraud: a follow-up to age 50 in a Dutch conviction cohort - Geest, Victor R. van der (European journal of criminology, 2017)
This study describes the criminal careers of offenders convicted of fraud, distinguishing different career dimensions such as intermittency, versatility and specialization. Results indicate that most fraud offenders are versatile in the sense that they also have significant criminal records for other serious offending (that is, not fraud). At the same time they are also specialized in fraud. When we examine developmental trajectories of serious offending and next explore patterns of fraud for the groups identified, we find that offenders in our sample represent a heterogeneous group and that the classic divide between typical financial (for example, white-collar) offenders and common criminals does not apply to the majority of our sample.